Plug-in electric vehicles what role for Washington? - Sandalow, David (Brookings Institution Press, 2009)
"Explains the current landscape for plug-in electrics and implications for national security, the environment, and the economy. Discusses what can and should be done by the U.S. government to advance the role of plug-in electric vehicles"--Provided by publisher.